Kedudukan Akta Notaris sebagai Alat Bukti Tertulis dalam Pembuktian Peralihan Hak atas Tanah Berdasarkan Sistem Publikasi Negatif Bersertifikat - Utari Amanda (Tolis Ilmiah : Jurnal Penelitian, 2026)
Legal certainty in land rights transfer under the certificated negative publication system faces problems regarding the position of notarial deeds as evidence, especially after the enactment of Government Regulation 18 of 2021 which has not fully accommodated the dynamics of proving land rights transfer. This research aims to analyze the position of notarial deeds as written evidence in proving land rights transfer and its legal implications for the legal protection of rights holders under the certificated negative publication system. The research method uses normative juridical approach with statutory and conceptual approaches, analyzing Law Number 2 of 2014 and Government Regulation Number 18 of 2021 along with scientific literature from 2020-2025. The research findings indicate that notarial deeds possess conditional perfect evidentiary power and play a complementary role with land certificates, providing preventive protection through structured documentation and repressive protection in litigation. The research concludes that optimization of legal protection requires comprehensive synchronization of notarial and land regulations at normative, institutional, technological, and professionalism levels, as well as gradual transition towards a positive publication system through Complete Systematic Land Registration.